2017
DOI: 10.1103/physrevb.96.205436
|View full text |Cite
|
Sign up to set email alerts
|

Origin of luminescence quenching in structures containing CdSe/ZnSe quantum dots with a few Mn2+ ions

Abstract: We present a detailed spectroscopic study of the photoluminescence quenching in an epitaxial structures containing CdSe/ZnSe quantum dots doped with low concentration of Mn 2+ ions. Our time-resolved and time-integrated experiments reveal the origin of the quenching observed in macrophotoluminescence studies of ensembles of such dots. We show that incorporation of even a few ions to an individual dot does not quench its luminescence effectively, although some fingerprints of expected spin-dependent quenching a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
7
0
3

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 55 publications
0
7
0
3
Order By: Relevance
“…Он объясняется существованием спиновых правил отбора для обменного механизма, из которых следует, что БПЭ ионам Mn 2+ , находящимся на нижнем, наиболее заселенном в магнитном поле спиновом подуровне, запрещена. Однако недавние исследования магнитофотолюминесценции одиночных CdSe/ZnSe КТ, содержащих несколько ионов Mn 2+ , указывают на то, что, наблюдаемый рост интенсивности может быть вызван и другими причинами, а его детали нуждаются в уточнении [4]. Возможно, при рассмотрении этого эффекта следует учитывать кинетику экситонов не только в КТ, но и в подложке, на которой они выращены.…”
Section: Introductionunclassified
See 2 more Smart Citations
“…Он объясняется существованием спиновых правил отбора для обменного механизма, из которых следует, что БПЭ ионам Mn 2+ , находящимся на нижнем, наиболее заселенном в магнитном поле спиновом подуровне, запрещена. Однако недавние исследования магнитофотолюминесценции одиночных CdSe/ZnSe КТ, содержащих несколько ионов Mn 2+ , указывают на то, что, наблюдаемый рост интенсивности может быть вызван и другими причинами, а его детали нуждаются в уточнении [4]. Возможно, при рассмотрении этого эффекта следует учитывать кинетику экситонов не только в КТ, но и в подложке, на которой они выращены.…”
Section: Introductionunclassified
“…Очевидно, что самым прямым доказательством доминирования обменного механизма является проверка выполнения правил отбора. До недавнего времени наиболее очевидным доказательством этого считался быстрый рост интенсивности ФЛ слоя CdMnSe/ZnSe КТ в поле B 0z, но, как сказано выше, недавние исследования указывают на то, что наблюдаемый рост интенсивности может иметь другие причины [4].…”
Section: Introductionunclassified
See 1 more Smart Citation
“…Consequently, relative intensity of each of these lines constitutes a convenient measure of the orientation of the TM ion spin. This particular feature has been exploited in a number of studies concerning various types of dopants in different semiconductor systems [7,[9][10][11][12][13][14][15][16][17]. Such an approach is naturally limited to the case of the non-resonant excitation, since in the resonant case the directly excited state is vastly over-represented in the photoluminescence spectrum [18,19].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, optical manipulation of a single magnetic ion spin is possible not only in classical systems with a single Mn 2+ ion in QDs with a relatively low energy gap, CdTe/ZnTe [2][3][4][5][6] and InAs/GaAs [7][8][9], but also in QDs with a higher-energy gap such as CdSe/ZnSe [1,[10][11][12] or in QD systems doped with impurities considered previously as killers of photoluminescence: Co 2+ [1], Fe 2+ [13,14], and Cr 2+ [15,16]. For all the systems studied so far it has been found that the ground state of the magnetic ion is significantly influenced by the local strain present in a quantum dot.…”
Section: Introductionmentioning
confidence: 99%